1996
DOI: 10.1006/jmbi.1996.0697
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structure of a Hyperthermophilic Archaeal TATA-box Binding Protein

Abstract: This study analyzes the three-dimensional structure of the TATA-box properties. The crystal structure of this hyperthermostable protein was Cambridge University, compared to its mesophilic homologs and analyzed for differences in the Cambridge, CB2 1QR, UK native structure that may contribute to thermostability. Differences found were: (1) a disulfide bond not found in mesophilic counterparts; (2) an increased number of surface electrostatic interactions; (3) more compact protein packing. The presumed DNA bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
139
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(151 citation statements)
references
References 48 publications
11
139
1
Order By: Relevance
“…We chose proteins for which both the crystal and NMR structures were available, either for the same structure or within the same protein family. Our analysis showed that all the protein structures solved by using crystallographic procedures had packing values lying within the narrow range of 0.34-0.37 ( Figure 5), as pointed out by DeDecker et al (38). The only exceptions were the well-packed hyperthermophilic TBP [packing value ) 0.375 (38)] and a metallothionein (packing value ) 0.25, 4MT2).…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…We chose proteins for which both the crystal and NMR structures were available, either for the same structure or within the same protein family. Our analysis showed that all the protein structures solved by using crystallographic procedures had packing values lying within the narrow range of 0.34-0.37 ( Figure 5), as pointed out by DeDecker et al (38). The only exceptions were the well-packed hyperthermophilic TBP [packing value ) 0.375 (38)] and a metallothionein (packing value ) 0.25, 4MT2).…”
Section: Resultssupporting
confidence: 73%
“…Our analysis showed that all the protein structures solved by using crystallographic procedures had packing values lying within the narrow range of 0.34-0.37 ( Figure 5), as pointed out by DeDecker et al (38). The only exceptions were the well-packed hyperthermophilic TBP [packing value ) 0.375 (38)] and a metallothionein (packing value ) 0.25, 4MT2). The crystal structures of proteins with different sequences but belonging to the same family showed very similar packing values (e.g., myoglobin: average, 0.35; standard deviation, 0.008).…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…2). As is typical for archaeal promoters, the TSS of each gene is a purine residue with an appropriately spaced TATA box centred approximately 25 bp upstream (DeDecker et al, 1996). However, none of the promoters have an obvious purinerich BRE element (Qureshi and Jackson, 1998), instead having pyrimidine-rich (~66%) sequences immediately upstream of the putative TATA boxes.…”
Section: Mtsd Mtsf and Mtsh Are Fusion Proteins With A Methyltransfementioning
confidence: 99%